Pregnancy in times of Pandemic: A look at Mental Health before and during the pandemic: Ser gestante en tiempos de pandemia: Una mirada de la salud mental antes y durante la pandemia - Cisneros Hilario, César B. (2022)
Introduction: Pregnancy is a time of physiological, psychological, personal and social changes for women. The role of the emotional and psychological aspect encompasses the entire period because as fetal development advances, the mother-baby relationship strengthens, making the mother vulnerable. Objectives: To collect, describe and analyze relevant information on mental health in pregnant women, both at different stages of gestation and before and during the COVID-19 pandemic. Methods: A literature search was conducted through PubMed, Google Scholar and Scielo using terminology compiled from MeSH and DeCs. Results: Pregnancy due to hormonal changes causes the presence of anxiety and depression that worsen as the stages of fetal development progress. These psychological disorders have greatly increased during the COVID-19 pandemic due to several reasons such as the relationship with the couple, uncertainty, fear, anguish and increasing phobia about contagion. Final considerations: Pregnant women are a vulnerable population, whose mental health has always been affected and nowadays it has been much more affected due to the pandemic, therefore they need better attention in the health sector such as providing them with reliable information on measures to alleviate the burden of stressors, since they not only carry the anguish of their health but also that of the fetus.